Institutionalizing archives management in the Philippine Information Agency (I-AM-PIA): training on government records administration disposition (Phase 1) - Mercurio, Hazel C.
One of the cornerstones of government accountability is the preservation of records. Reliable records are vital in delivering public institutions’ function and services. They serve as documentation of the actions taken and decisions made by government officials and show the process of how these decisions were made. Preserving these records also ensures that future generations will have access to past government activities, which forms a part of a country’s history. A way to ensure reliable record-keeping is by stablishing an institution dedicated to records and archives management.